Quercetin Ameliorates Renal Fibrosis via SIRT5 in Diabetic Nephropathy (Iranian Journal of Kidney Diseases, 2025)
Objectives: Renal fibrosis represents the principal pathological characteristic of diabetic nephropathy (DN). Quercetin, a well-known flavonoid with diverse pharmacological effects, has been studied for its link to preventing DN. Previous studies indicated that SIRT5 might have significant implications in fibrotic diseases. This study investigated whether the protective effects of quercetin on DN was related to SIRT5.Methods: Three doses of quercetin (30 mg/kg, 60 mg/kg, and 120 mg/kg) were orallyadministered to streptozotocin-induced diabetic rats over a period of four months. Colorimetric methods were used to measure blood urea nitrogen (BUN), serum creatinine (SCr) and urine creatinine (UCr). Enzyme-linked immunosorbent assay (ELISA) was used to quantify the level of urine microalbumin (Ualb). The ratio of urine microalbumin to urine creatinine (Ualb/UCr) was calculated. Periodic acid-Schiff (PAS) stain and Masson's trichrome stain were used to observe glycogen deposition and collagen accumulation in the renal cortex, respectively. Western blot, ELISA, and immunohistochemical stain were performed to quantify the levels of SIRT5 protein in kidneys of rats.Results: Diabetic rats exhibited increased levels of SCr, BUN, and Ualb/UCr, accompanied by significant glycogen deposition and collagen accumulation in renal cortex. These changes were associated with an increased level of SIRT5 protein. Following treatment of DN rats with varying doses of quercetin, all kidney function and pathology indices showed varying degrees of reversal, accompanied by a reduction in SIRT5 protein levels.Conclusion: Quercetin ameliorated renal fibrosis in DN rats via the inhibition of SIRT5, suggesting a novel mechanism of quercetin in the treatment of DN.